Architectures neolithiques de l'ile d'Yeu (Vendee) (ARCHAEOPRESS, 2021)
This volume gathers documentation, unpublished material and the principal results of studies, prospections, excavations and surveys carried out on domestic settlements, funeral monuments, quarries and symbolic sites on the Isle of Yeu Situated off the Atlantic coast of the Vendée (France).